The Relationship of Self Confident with Result Learn of Poor Students - Widya Aprilia; Firman Firman (Jurnal Neo Konseling, 2020)
This research was aimed to examine the correlation beetwen self confidence and result learn of poor students among senior high school students. This research was a quantitative study which involved all student off poor in SMA N 3 Padang with the total number of 61 students. The instrument use to collect data were self confidence and result learn scales. Data were analyze using Rank Spearman techniques with the help of the SPSS 21 program. The result shows that the coefficient correlation is 0,972 (r=0,972) in the significant level of 0,000 (p=0,000). The result means that there is correlation positive and significant between self confidence and result learn in which the relation between both variable is unidirectional. So, the higher the self confidence student have, the higher their result learn would be and vice versa.